조직학적 진단에 따른 악성종양의 분류 및 분포 : 국립의료원 자료를 중심으로 한 통계적 고찰 - 박충서 (연세대학교 보건대학원, 1986)
[한글] 1975년 1월부터 1984년 12월까지 만 10년간 국립의료원에 내원한 환자중 병리조직학적인 검사로서 악성종양으로 확진된 4,577예에 대하여 WHO의 ICD-O분류법에 따라 분류, 이들을 부호화한 다음 성별 및 연령별분포, 장기별 빈도, 년도별 증감 등에 관해 전산처리하여 다음과 같은 결과를 얻었다. 1. 1975년 부터 1984년까지 국립의료원에서 악성종양으로 확진된 예는 총 4,577예로서 같은 기간 동안 조직검사가 시행되었던 33,193예중의 13.8%였으며, 총 조직검사수에 대한 비율은 1979년 이전이 1980년 이후보다 높았다. 2. 악성종양의 성별분포는 남자 2,280예(49.8%), 여자 2,297예 (50.2%)로 남녀의 비는 1:1이었고 성별에 따른 평균연령에는 유의한 차이가 없었다. 3. 원발성 악성종양은 3,409예였으며 이들의 장기별 빈도 순위는 전체적으로 위암 788예 (23.1%), 자궁경부암 650예 (19.1%), 대장·직장암 248예 (7.3%), 피부암 176예 (5.2%), 유방암 163예(4.8%)의 순위를 보였으며 남자에서는 위암 483예 (30.0%), 대장·직장암 142예 (12.2%), 피부암 114예 (7.1%), 폐암 112예(7.0%), 간암 107예(6.6%)등의 순위였고, 여자에서는 자궁경부암 650예 (36.1%), 위암 305예 (17.0%), 유방암 162예 (9.0%), 대장·직장암 106예 (5.9%), 갑상선암 96예(5.3%)의 순서를 보였다. 4. 위암으로 위절제술이 시행되었던 206예 중에는 기위암이 21예, 침습암이 185예었으며 자궁경부암 650예 중에는 상피내암이 145예, 미소침습암이 26예, 침습암이 479예였다. 이상의 결과를 종합하면 조직검사수에 대한 악성종양의 비율이 감소하고 우리나라의 악성종양중 가장 많던 자궁경부암의 점차적인 감소, 위암의 상대적인 증가 및 자궁경부암 중 상피내암 비율의 증가경향을 알 수 있으며 이는 진단방법의 개선 및 적극성과 환자의 악성종양에 대한 인식의 향상 때문으로 사료된다. [영문] During ten years from January, 1975 to December, 1984, 4577 cases of malignant neoplasm were diagnosed by histopathologic examination in National Medical Center. These cases were classified by the International Classification of Disease for Oncology (ICD-0) published by World Health Organization. All data have been coded, computerized and analysed about distributions by sex, age and organ or tissue of origin, and about annual changes of frequency. The results obtained were as follows: 1. During ten years from 1975 to 1984, the total number of cases rendered to pathologic diagnosis in National Medical Center was 33,193 and malignant neoplasm occupied 13.8% (4577 cases) of these. The relative frequency of malignant neoplasm to surgical specimen was higher before 1979 than after 1980. 2. Among 4577 malignancy, 2280 patients were male and 2297 were female. There was no sex difference in the mean age. 3. The total number of primary malignant neoplasm was 3409 and the most prevalent organ of malignancy was stomach(788 cass, 23.1%), which was followed by cervix (650 casas, 19.1%), colo-rectum (248 cases 7.3%), skin(176 cases, 5.2%) and breast (163 cases, 4.8%), in the order of frequency. In male, five leading frequent site of primary malignant neoplasm were stomach (483 cases, 30.3%), colo-rectum (142 cases, 12.2%), skin (114 cases, 7.1%), lung (112 cases, 7.0%), and liver (107 cases, 6.6%). In female, the most frequent site was uterine cervix (650 cases, 36.1%), followed by stomach (305 case, 17.0%), breast (162 cases, 9.0%), colo-rectum (106 cases, 5.9%), and thyroid (96 cases, 5.3%). 4. In 206 cases of stomach cancer, in which the diagnosis was made by subtotal gastrectomy specimen, 21 were early stomach cancers and 185 cases were advanced cancers. Six hundred fifty cases of uterine cervical cancer included 145 cases of in situ lesion, 26 cases of microinvasion and 379 cases of infiltrative cancer. In summary, the relative frequency of malignant neoplasm to surgical specimen is decreasing, and the stomach cancer seems to be increasing. The uterine cervical cancer decreases with a relative increasing of in situ lesion. It is thought that the active attitude and improvement of diagnostic method and increased awareness of patients about malignant neoplasm reflect the present results.
보건학과/석사